Stormtroopers : a new history of Hitler's Brownshirts - Siemens, Daniel 1975- (Yale University Press, 2017)
Introduction: a night of violence -- Turmoil in post-war Germany and the origins of the Nazi SA -- Stormtrooper street politics: mobilization in times of crisis -- The SA cult of youth and violence in the Weimar Republic -- Terror, excitement, and frustration -- The "Röhm purge" and the myth of the homosexual Nazi -- The transformation of the SA between 1934 and 1939 -- Streetfighters into farmers? The SA and the "Germanization" of the European east -- Stormtroopers in the Second World War -- SA diplomats and the Holocaust in Southeastern Europe -- "Not guilty": the legacy of the SA in Germany after the Second World War -- Conclusion: the SA and National Socialism